HIGHEST AND BEST USE ANALYSIS FOR REDEVELOPING THE ECONOMICAL SUSTAINABLITY OF HIGH-RISE BUILDING - MD RIZA, FARAH NABILAH (Universiti Teknologi PETRONAS, 2020)
The highest and best use is a method used to evaluate the legitimate use of vacant land or improved property which is physically probable, financially feasible, maximally competitive, and which results in the highest value. Highest and best use analyses provide a link between economics, statistics, and real applications, locations, and requirements of investors. The case study of this research has been taken at Menara Raja Laut, Kuala Lumpur. This office building has a problem with the low occupancy. With the details that have been collected, Menara Raja Laut still in good condition and suitable to do the redevelopment with a few alternatives. The objectives of this research were to identify the possible alternatives for the building use for Menara Raja Laut redevelopment, to evaluate the highest and best use decision-making model, and to validate the highest and best alternatives for Menara Raja Laut.